Neurotuberculosis: A Clinical Review - Chin, Jerome H. (Seminars in Neurology, 2019)
In September 2018, the United Nations General Assembly held the first ever meeting to discuss the global epidemic of tuberculosis (TB) and adopted a political declaration titled “United to end tuberculosis: an urgent global response to a global epidemic.” The timing of the meeting was prescient but overdue since Mycobacterium tuberculosis surpassed the human immunodeficiency virus as the world's leading infectious killer in 2014. Infection of the central nervous system by Mycobacterium tuberculosis, herein referred to as neurotuberculosis, is the most feared and dangerous form of tuberculosis, requiring a high level of suspicion and clinical experience for prompt diagnosis and treatment. Neurologists, infectious disease specialists, orthopedic surgeons, neurosurgeons, and hospitalists in all countries need to recognize the spectrum of neurotuberculosis and be able to integrate clinical information, laboratory data, and radiological findings to make a diagnosis with or without microbiological confirmation.
Keywords: tuberculosis; meningitis; cerebrospinal fluid; HIV; Xpert